Educational Support Around Dialysis Modality Decision Making in Patients With Chronic Kidney Disease: Qualitative Study. Issue 1 (October 2018) - Cassidy, Brendan P.; Harwood, Lori; Getchell, Leah E.; Smith, Michael; Sibbald, Shannon L.; Moist, Louise M.
Background: Patients with chronic kidney disease (CKD) are asked to choose a renal replacement therapy or conservative management. Education and knowledge transfer play key roles in this decision-making process, yet they remain a partially met need. Objective: We sought to understand the dialysis modality decision-making process through exploration of the predialysis patient experience to better inform the educational process. Design: Qualitative descriptive study. Setting: Kidney Care Centre of London Health Sciences Centre in London, Ontario, Canada. Patients: Twelve patients with CKD, with 4 patients on in-center hemodialysis, home hemodialysis, and peritoneal dialysis, respectively. Measurements: Not applicable. Methods: We conducted semistructured interviews with each participant, along with any family members who were present. Interviews were transcribed verbatim. Conventional content analysis was used to analyze the transcripts for common themes. Representative quotes were decided via team consensus. A patient collaborator was part of the research team. Results: Three themes influenced dialysis modality decision making: (i) Patient Factors: individualization, autonomy, and emotions; (ii) Educational Factors: tailored education, time and preparation, and available resources; and (iii) Support Systems: partnership with health care team, and family and friends. Limitations: Sample not representative of wider CKD population. Limited number of eligible patients. Poor recall may affect findings. Conclusions: Modality decision making is a complex process, influenced by the patient's health literacy, willingness to accept information, predialysis lifestyle, support systems, and values. Patient education requires the flexibility to individualize the delivery of a standardized CKD curriculum in partnership with a patient-health care team, to fulfill the goal of informed, shared decision making.